Expeller soybean meal as a source of rumen undegradable protein for lactating dairy cows - John E. Shirley; D. Piehl; Evan C. Titgemeyer; Michael V. Scheffel (Kansas Agricultural Experiment Station Research Reports, 1997)
The loss of meat and bone meal as a source of high quality protein for lactating cows creates an increased need for nonanimal sources. Fifty six Holstein cows were used to evaluate expeller soybean meal as a source of rumen undegradable intake (by-pass) protein for high producing cows. Expeller soybean meal tended to improve 3.5% contain fat-corrected milk yield and increased milk fat percentage relative to diets containing either solvent soybean meal or a meat and bone meal:blood meal mixture. In contrast, the protein percentage in milk was depressed significantly when cows were fed expeller soybean meal compared to animal protein. A limiting amino acid (possibly methionine) is implicated.; Dairy Day, 1997, Kansas State University, Manhattan, KS, 1997;
Keywords: Dairy Day; 1997; Kansas Agricultural Experiment Station contribution; no. 98-100-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 792; Dairy; Lactating cows; UIP; Expeller soybean meal